Affirmative action policies at UFSC: progress towards addressing institutional racism and achieving racial equity - Passos, Joana Célia dos (2025)
The Federal University of Santa Catarina has a long history with affirmative policies. This article aims to reflect on the seventeen-year trajectory and the impacts of affirmative actions for black, Indigenous and quilombola people at the UFSC, In terms of combating Institutional racism. It also aims to present its policy for combating Institutional racism, and the protocols established to implement anti-racist practices that are being gradually implemented at the university as a mechanism for building the promotion of racial equity.